Lhermitte's sign in multiple sclerosis: a clinical survey and review of the literature. Issue 4 (April 1982) - Kanchandani, R; Howe, J G
Abstract : Lhermitte's sign was experienced by 33.3% of 114 patients with multiple sclerosis, and in 16% it occurred in the first episode. Eleven patients with subacute combined degeneration of the cord due to pernicious anaemia also were reviewed, and one reported Lhermitte's sign. Review of the literature suggests that the symptom rarely occurs in other conditions except subacute combined degeneration of the cord, neck trauma, radiation myelitis and prolapsed cervical disc.